The Model Of Religious Moderation In Social Life: Study of Living Religion in Badongan, Kudus - Zuhri, Achmad; Bakhruddin, A. (LPPM IAIN Kudus, 2021)
This study explain the model of religious moderation in social life with the concept of living religion in Badongan community, at Tumpangkrasak village, Kudus Central Java. Here, people of Badongan are heterogeneous community consisting of interfaith even cross ethnicity. As known, Badongan has a mosque and two churches that are close together, but this does not necessarily cause conflict and clash because of a difference of their beliefs. This study uses descriptive qualitative method; the data is done by interview, and observation. The results of this study indicate that the religious moderation model has been strengthening tolerance values, eliminating social barriers in social activities, and getting along in harmony in every social activity. Such behavior can be entrenched because it is inseparable from the advice of the ancestors of Badongan who prioritize tolerance between religion communities, the view of citizens in society is far from negative attitudes and good communication between members of the community.